PENGARUH PERTUMBUHAN EKONOMI DAN TINGKAT PENDIDIKAN TERHADAP KEMISKINAN MELALUI TINGKAT PENGANGGURAN DI KABUPATEN MIMIK - Rifka Rifka; Marlen Helena Pello; Yuliana Jelita Heatubun (CV. Adiba Aisha Amira, 2026)
This study aims to analyze the effect of economic growth and education level on poverty through the unemployment rate in Mimika Regency. The study employs a quantitative approach using path analysis estimated through multiple linear regression. The data used are secondary time-series data covering a fifteen-year period, obtained from the Central Bureau of Statistics of Mimika Regency and Papua Province. The analysis consists of two structural equations, where the first equation examines the effect of economic growth and education level on unemployment, while the second equation analyzes the effect of economic growth, education level, and unemployment on poverty. The results of the first structural model indicate that economic growth and education level have a negative and significant effect on unemployment. Meanwhile, the results of the second structural model show that economic growth, education level, and unemployment simultaneously affect poverty, although partially each variable does not show a statistically significant effect. The findings indicate that unemployment plays an intervening role in explaining the relationship between economic growth, education level, and poverty in Mimika Regency. These results suggest that poverty reduction policies should not only focus on economic growth and education improvement but also emphasize job creation to ensure a more inclusive development process.